2001
DOI: 10.1021/ic010849w
|View full text |Cite
|
Sign up to set email alerts
|

Bromite Ion Catalysis of the Disproportionation of Chlorine Dioxide with Nucleophile Assistance of Electron-Transfer Reactions between ClO2 and BrO2 in Basic Solution

Abstract: The rate of ClO(2) conversion to ClO(2)(-) and ClO(3)(-) is accelerated by BrO(2)(-), repressed by ClO(2)(-), and greatly assisted by many nucleophiles (Br(-) > PO(4)(3-) > HPO(4)(2-) > CO(3)(2-) > Cl(-) approximately OH(-) > CH(3)COO(-) approximately SO(4)(2-) approximately C(5)H(5)N >> H(2)O). The kinetics (at p[H(+)] = 9.3-12.9) show that the first step of the mechanism is an electron transfer between ClO(2) and BrO(2)(-) (k(1) = 36 M(-1) s(-1)) to give ClO(2)(-) and BrO(2). This highly reversible reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…The measured pH was converted to p[H + ] on the basis of electrode calibration at μ = 1.0 M (NaClO 4 ). Ion chromatographic data were obtained with a Dionex DX-500 instrument as described previously . UV−vis spectra and kinetic scans were obtained on a Perkin-Elmer Lambda-9 UV−vis−NIR spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measured pH was converted to p[H + ] on the basis of electrode calibration at μ = 1.0 M (NaClO 4 ). Ion chromatographic data were obtained with a Dionex DX-500 instrument as described previously . UV−vis spectra and kinetic scans were obtained on a Perkin-Elmer Lambda-9 UV−vis−NIR spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
“…The electrode potentials in basic solution for the two-step reduction of BrO 2 - and ClO 2 - by SO 3 2- are shown in eqs 7−10 . The BrO 2 - /OBr - potential is calculated on the basis of the BrO 3 - /OBr - , BrO 2 /BrO 3 - , and BrO 2 - /BrO 2 couples. The thermodynamic driving forces for the BrO 2 - /SO 3 2- and the ClO 2 - /SO 3 2- reactions are comparable.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that many different nucleophiles (Nu's) catalyze the electron transfer from ClO 2 to BrO 2 where third-order rate constants increased 4 orders of magnitude from the weakest nucleophile studied (H 2 O) to the strongest (Br - ) . It was postulated that the nucleophile effect need not be specific to the system studied but may be a more common phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon was first reported for the disproportionation of ClO 2 and the reaction of ClO 2 with BrO 2 . 23 In a subsequent report, it was shown to occur in the reaction of ClO 2 with NO 2 also. 179 We use the latter reaction to illustrate the mechanism: the net reaction of NO 2 with ClO 2 yields NO 3 À and ClO 2 À , and its rates are a strong function of the concentrations of various nucleophiles such as NO 2 À , Br À , CO 3 2À , and so on.…”
Section: Nucleophile-assisted Electron Transfer Reactionsmentioning
confidence: 91%
“…ClO 2 disproportionates, but only with the assistance of nucleophiles. [23][24][25] Three pathways are found in the mechanism. The first path has a rate law that is first order in [ClO 2 ] and [OH À ] and yields ClO 2 À þ ClO 3 À ; it is inferred to have addition of OH À to ClO 2 as the rate-limiting step with disproportionation occurring in a rapid reaction of this adduct with ClO 2 .…”
Section: Disproportionationmentioning
confidence: 99%